Consequences of bullying on university students in Bangladesh - Rahman, Mostafizur; Hasan, Monjurul; Hossain, Alamgir; Kabir, Zahangir (Zielona Góra: Faculty of Economics and Management Press)
Bullying at university is a pervasive phenomenon that has negative outcomes on the psychological and actual wellbeing of students, their success and achievement. The examination expected to research the consequences of bullying on university level students. A self-administrated survey was planned by the exploration goals and theories. The sample size consists of 380 students randomly selected from different faculties of a public university in Bangladesh.
Keywords: HEIs; higher education; students; bullying; symptom; academic achievements; Bangladesh; uczelnia wyższa; szkolnictwo wyższe; zastraszanie; objawy; osiągnięcia naukowe; Bangladesz